THE ROLE OF “MATRICULATION” AS INFLUENTIAL FACTOR CONTRIBUTING TO THE STUDENTS’ ENGLISH PERFORMANCE - Nina Afrida; Shafrida Waty; Nurul Hidayani (ELITE Association Indonesia, 2019)
“Matriculation” program is a program held by Language Development Institution of IAIN Langsa to prepare and to check the students’ basic knowledge of English. This paper reports the contribution and influence of “Matriculation” program to the students’ English performance. 60 students from 12 different fields at IAIN Langsa during the 2014-2015 academic year and 10 lecturers were chosen as samples. Data were collected using questionnaire, interview and document, and analyzed by using mixed method. The findings indicate that there is only weak and limited contribution of “Matriculation” to the students’ English performance.